TELAAH LITERATUR TENTANG DAKWAH DI INDONESIA - Alamsyah; Mery Yanti (LP2M Universitas Ibrahimy, 2019)
Da'wah is one of the important elements in all religions. In Indonesia, a lot of research on da'wah has been done by scientists, but no one has tried to map the results of knowledge that have been done by these researchers. Therefore, this article aims to get an idea of the theoretical knowledge that has been produced by da'wah researchers in Indonesia. From the results of an analysis of 44 articles that became the sample of the study, we concluded that the phenomenon of da'wah was studied in a more descriptive qualitative manner. The focus of the research is still limited to the issue of exclusive preaching messages and the practice of preaching carried out by civil society. Research on exclusive preaching messages, aspects of preaching management and organization, and preaching activities of government institutions and private corporations are rarely explored. The researcher discusses the theoretical and practical implications of these findings for the world of research and scientific publications in Indonesia.